The Role of Ultrasound Elasticity Imaging in Predicting Ileal Fibrosis in Crohn's Disease Patients. Issue 11 (November 2015) - Fraquelli, Mirella; Branchi, Federica; Cribiù, Fulvia Milena; Orlando, Stefania; Casazza, Giovanni; Magarotto, Andrea; Massironi, Sara; Botti, Fiorenzo; Contessini-Avesani, Ettore; Conte, Dario; Basilisco, Guido; Caprioli, Flavio
Abstract : Backgound: Bowel wall fibrosis is associated with a complicated disease behavior in patients with Crohn's disease (CD). The quantitative assessment of fibrosis severity in CD-affected bowel can help clinical decision making. Our aim was to evaluate the feasibility, reliability, and reproducibility of ultrasound elasticity imaging (UEI) toward the assessment of ileal fibrosis in CD patients. Methods: Twenty-three consecutive patients with ileal or ileocolonic CD, elected for surgical resection of the terminal ileum, underwent bowel ultrasound and UEI. Twenty inflammatory CD patients without complications were enrolled as controls. Bowel wall stiffness was evaluated with UEI by means of color scale and quantitative strain ratio measurement. The severity of bowel wall fibrosis and inflammation were evaluated on histological sections by semiquantitative and quantitative image analysis and used as a reference standard. Results: The UEI strain ratio measurement was significantly correlated with the severity of bowel fibrosis at both semiquantitative and quantitative histological image analysis: it was characterized by an excellent discriminatory ability for severe bowel fibrosis (area under the receiver operating characteristic curve: 0.917; 95% confidence interval, 0.788–1.000). UEI strain ratio measurements were characterized by an excellent interrater agreement. At multivariate analysis, bowel wall fibrosis proved the only independent determinant of the strain ratio. The ileal strain ratio of inflammatory CD patients was significantly lower than in operated CD patients with severe fibrosis. Conclusions: UEI can be used to assess ileal fibrosis in CD patients. Abstract : Article first published online 30 July 2015.Supplemental Digital Content is Available in the Text.